The Implementation of Customer Relationship Marketing Strategy on Customer Satisfaction in KPRI Budi Luhur Lamongan - Dhita Dhora Damayanti (Jurnal Mantik, 2020)
"The Effect of Customer Relationship Marketing Strategy Implementation on Customer Satisfaction at KPRI Budi Luhur Lamongan". The purpose of this thesis is to determine the relationship between Customer Relationship Marketing variables and customer satisfaction either jointly or partly at KPRI Budi Luhur Lamongan from 2016 to 2019. From this research variable, it will be obtained which variable is the most dominant in customer satisfaction. The research object uses the method of observation, interviews, and documentation. While the data analysis technique uses the Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Correlation Test, Coefficient of Determination, t test, F test. or partly at KPRI Budi Luhur Lamongan from 2016 to 2019. From this research variable, it will be obtained which variable is the most dominant in customer satisfaction.